Applicability of glucocorticoid toxicity index in pemphigus: Comparison between two groups of rituximab‐treated and rituximab‐naïve patients. Issue 12 (17th October 2022) - Mazaherpour, Elham; Kianfar, Nika; Dasdar, Shayan; Sedaghat, Mojtaba; Seyrafi, Hassan; Balighi, Kamran; Saberi, Fatemeh; Nili, Ali; Farimani, Zeinab; Azar, Pedram Molhem; Mahmoodi, Hamidreza; Murrell, Dedee F.; et al.
Abstract: Rituximab (RTX) combined with short‐term glucocorticoids (GC) is an effective therapeutic option for pemphigus. The newly developed Glucocorticoid Toxicity Index (GTI) tool provides the possibility to measure GC toxicities over time. To compare 1‐year GTI between two groups of RTX‐treated and RTX‐naïve patients with pemphigus. The responsiveness of the GTI was also investigated. A prospective cohort of 129 adults with newly diagnosed pemphigus was conducted. GC‐related toxicities were assessed at 3‐month intervals according to Composite and Specific lists of the GTI. Of the patients, 76.7% ( n = 99) received RTX. Throughout the time intervals, RTX‐treated patients had lower GTI compared to RTX‐naïve ones ( p = 0.036). The mean GTI at 1‐year was 34.3 in the RTX‐treated group and 50.8 in the RTX‐naïve group ( p = 0.04). The most commonly observed GC‐related toxicity was neuropsychiatric manifestations for 34% (224 events). The relapse rate of RTX‐treated patients (1%) was significantly lower than RTX‐naïve patients (10%) ( p = 0.037). The GTI showed no correlation with cumulative GC consumption in both groups ( p > 0.05, both). Patients treated with GC alone had remarkably higher GTI than patients treated with GC plus RTX. The GTI is an applicable tool to quantitatively capture GC toxicities at the patient level in pemphigus.